Regulatory Role of RNA N6-Methyladenosine Modification in Bone Biology and Osteoporosis - Chen, Xuejiao; Hua, Wenfeng; Huang, Xin; Chen, Yuming; Zhang, Junguo; Li, Guowei (Frontiers in Endocrinology, 2020)
Osteoporosis is a metabolic skeletal disorder in which bone mass is depleted and bone structure is destroyed to the degree that bone becomes fragile and prone to fractures. Emerging evidence suggests that N6-methyladenosine (m6A) modification, a novel epitranscriptomic marker, has a significant role in bone development and metabolism. In this review, we summarize the most up-to-date evidence of m6A RNA modification in osteoporosis and highlight the potential role of m6A in prevention, treatment and management of osteoporosis.